REAL OPTIONS: AN APPROACH TO EVALUATE INVESTMENT OPPORTUNITIES - Del Carpio Gallegos, Javier (2004)
This article deals about how real options' evaluation can be used to evaluate investment opportunities, with the purpose of providing the decision takers with a tool allowing organizations to face more complex situations.